Identifying the action ways of function materials in catalyzing organic waste transformation into humus during chicken manure composting. (May 2020) - Wu, Junqiu; Zhao, Yue; Wang, Feng; Zhao, Xinyu; Dang, Qiuling; Tong, Tianjiao; Wei, Zimin
Graphical abstract: Highlights: Functional materials (FM) disturb the effect of precursors on humus formation. Adding FM in early stage of composting can promote organic waste reduction. Adding FM in later stage of composting is beneficial to raise humus production. FM promote humus formation by abiotic ways. Abstract: The aim of this study is to detect the action properties of functional materials (FM) in transforming waste into resource products with high humus content. FM (MnO2 and reducing sugar) were added in different periods of chicken manure composting. During composting, concentration of humic acids (HA) as aromatic fraction of humus, was increased by FM. The promotive effects of adding FM in later period was the most obvious. While adding FM in the beginning period could accelerate organic matter degradation, but it did not promote HA formation. Meanwhile, the microbial diversity was higher in groups by adding FM in the beginning and thermophilic periods. Therefore, it was speculated that FM might improve HA formation by promoting the abiotic polymerization of precursors. Eventually, structural equation model showed that FM was beneficial to abiotic pathway of HA formation. But the formation efficiency was reduced by interfering with biotic pathway.